Response of Recirculating Saltwater Aquariums to Long-Term Formalin Treatment - Knight, Stacy Jean; Boles, Larry; Stamper, M. Andrew (Journal of Zoo and Aquarium Research, 2016)
This study documents the degradation of formalin in saltwater recirculating systems and the response of the biological filter during a five-day 25 ppm formalin treatment regimen. A total of nine additions of formalin was administered over the course of five days. The target concentration was 25 ppm and frequent water sampling documented the degradation. Degradation rates changed over time (0.689–7.495 formalin ppm·hr-1) and results revealed frequent periods below therapeutic concentrations. Removal rates were not statistically different in systems with different bacterial diversity or systems with increased fish density. The results suggest the need for frequent testing and follow-up additions during treatment cycles to ensure therapeutic concentrations and prevent recurrence of pathogens.